Translationally Invariant Slip-Spring Model for Entangled Polymer Dynamics - Chappa, Veronica Cecilia (2012)
The topological effect of noncrossability of long flexible macromolecules is effectively described by a slip-spring model, which represents entanglements by local, pairwise, translationally invariant interactions that do not alter any equilibrium properties. We demonstrate that the model correctly describes many aspects of the dynamical and rheological behavior of entangled polymer liquids, such as segmental mean-square displacements and shear thinning, in a computationally efficient manner. Furthermore, the model can account for the reduction of entanglements under shear.